Influence of ultrasonic vibrations on lactic acid bacteria in the manufacture of bioyogurt - Doroshenko, Yevhenii; Yastremska, Larysa (Problems of Environmental Biotechnology, 2021)
The results of research of influence of ultrasonic fluctuations on lactic acid bacteria at manufacturing of laboratory bioyogurt are presented.